Faktor Perilaku Memengaruhi Pemanfaatan Pelayanan Kesehatan Masyarakat Miskin di RSUD Gunungsitoli Kabupaten Nias Tahun 2019 - Indah - Anggraini (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
Utilization of hospital services in Indonesia, especially for the poor is still not optimal, this is due to several factors and behaviour that do not allow the public to utilize health services in hospitals. This study aims to determine the correlation and effect of knowledge, information, cost, transportation, and family support on health services utilization in Gunungsitoli Hospital Nias District 2019. This type of this study was survey quantitative methods used cross-sectional approach. The number of samples of 92 respondents who used reference had been taken proportionally and then selected using simple random sampling technique. Data were collected using a questionnaire that has been tested for validity and reliability with a total of 47 questions. Statistical test of each variable used chi-square with a significant level of 95% while the most influential variables are tested with logistic regression with a significant level of 95%.. The chi-square test showed that knowledge, information, transportation, and family support related on health services utilization in Gunungsitoli Hospital Nias District 2019. Based on the results of logistic regression found that there are two factors that most influence of health services utilization in Gunungsitoli Hospital Nias District 2019: knowledge and family support. It is recommended to the Nias District Government to monitor health programs aimed in increasing family and community knowledge in efforts to utilize health services. It is recommended for the Nias District Health Office to be more active in providing health education by collaborating with Gunungsitoli Hospital and puskesmas in the Nias District area.